Physical properties of polyethyleneimine-alginate gels - Mohamed, Suhaila; Salleh, Abu Bakar (Kluwer Academic Publishers, 1982)
The procedure for preparation of polyethyleneimine (PEI)-alginate gel and some of its physical properties are presented. The rigidity modulus (G) of the gel appears to increase to the second power of PEI concentration. Shrinkage is linearly related to pH up to pH 6.0. G increases as the pH is lowered, and decreases after freezing. The gels does not dissolve on heating and are strong, but fairly brittle. They are resistant to proteolytic enzymes.